NISBAH HARA MIKRO TERHADAP KALIUM DAUN BEBERAPA VARIETAS PADI (Oryza sativa L.) PADA DUA JENIS TANAH - Yustisia Yustisia; Tohari Tohari; Dja’far Shiddieq; Subowo G. (Widyariset, 2014)
Pot experiment was conducted at the experimental farm of Agriculture Faculty, Gadjah Mada University, Yogyakarta and aimed to investigate the effect of soil types, varieties and  and their interaction on Fe/K, Mn/K, Cu/K and Zn/K leaf, growth, leaf protein and grain yield of rice. The experiment was set up in a 2 x 6 factorial pat- tern randomized completely block design with three replications. First factor was two soil types viz. Vertisols and Inceptisols, second factor was rice varieties viz. Cimelati, Pandan Wangi, Ciherang, Cisokan, Widas and IR 64. The result revealed that the Fe/K, Cu/K and Zn/K ratios in rice leaf was significantly affected by soil types and rice varieties. The interaction of soil and rice varieties significantly affected the leaf ratios of Fe/K, Cu/K and Zn/K, crop growth rate (CGR) and grain yield, but it was not significantly affect the Mn/K ratio and leaf protein. The leaf ratios of Fe/K, Cu/K and Zn/K, CGR and grain yield in Vertisols were significantly higher than those in Inceptisols, while Mn/K ratio and leaf protein was significantly higher in Inceptisols. The highest of grain yield was achieved by Pandan Wangi whereas the lowest of grain yield was achieved by IR 64. The lowest of grain yield was achieved by IR 64 in Inceptisols. It was affected by an imbalance of Mn/K ratio and highest of leaf protein. It could be due to the effect of Inceptisols native soil properties (lower pH, higher Mn and K) and specific characteristics of IR 64 (more responsive to low pH, higher NH +  uptake). It was also may be caused by indirect effect of urea excess and KCl fertilizers on reducing of rhizosphere pH. The Mn/K ratio was important nutrient imbalance in Inceptisols soil and rice plant. The finding of this study suggests that the research in depth which is focused on Mn/K ratio balance in Inceptisols is needed, i.e using urea and KCl application in proper rate, using another source of nitrogen and potassium fertilizers, and using specific of varieties (less responsive to NH + and more responsive to NO -).